1993
DOI: 10.1105/tpc.5.5.531
|View full text |Cite
|
Sign up to set email alerts
|

An S receptor kinase gene in self-compatible Brassica napus has a 1-bp deletion.

Abstract: S locus glycoprotein (SLG) and S locus receptor kinase (SRK) cDNAs were isolated from an S allele present in a number of self-compatible Brassica napus lines. This Aí0 allele did not segregate with self-incompatibility in crosses involving other self-incompatible B. napus lines. The SLG-Aí0 cDNA was found to contain an intact open reading frame and was predicted to encode an SLG protein with sequence similarities to those previously associated with phenotypically strong self-incompatibility reactions. SLG-Aí0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(65 citation statements)
references
References 22 publications
(22 reference statements)
2
61
1
1
Order By: Relevance
“…However, as the scfl mutation affects the expression level of at least three S genes (SLG, SLR and SLR2), it is not possible to attribute the modification of the self-incompatibility reaction exclusively to the SLG gene. On the other hand, it has been recently reported that mutations at the SRK gene, which would lead either to a non functional protein kinase in B. napus [ 10] or to the absence of SRK expression in B. oleracea and B. campestris [20], were associated with a self-compatibility character. This observation argues in favour of the SRK gene playing a key role in self-incompatibility.…”
Section: Particular Expression Of the Slg Gene In The $2 Haplotypementioning
confidence: 99%
“…However, as the scfl mutation affects the expression level of at least three S genes (SLG, SLR and SLR2), it is not possible to attribute the modification of the self-incompatibility reaction exclusively to the SLG gene. On the other hand, it has been recently reported that mutations at the SRK gene, which would lead either to a non functional protein kinase in B. napus [ 10] or to the absence of SRK expression in B. oleracea and B. campestris [20], were associated with a self-compatibility character. This observation argues in favour of the SRK gene playing a key role in self-incompatibility.…”
Section: Particular Expression Of the Slg Gene In The $2 Haplotypementioning
confidence: 99%
“…Therefore, it is believed that SI is also regulated by genes other than the S-genes. A one-base deletion or an alternative transcript of the SRK gene located at the S-locus resulted in a low level of SI (Göring et al 1993;Tantikanjana et al 1993), and the m gene unlinked to the S-gene was related to the level of SI (Ikeda et al 1997). In addition, estimates of genetic factors have been performed using the wild population in order to gain an understanding of the evolution of the plant breeding system (Good and Stephenson 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Both genes are expressed speci®cally in the stigma papillae cells and they are thought to be responsible for the female side of the SI phenotype when the communication between pistil and pollen begins (Nasrallah and Nasrallah 1993;Nasrallah et al 1994a). The expression of SLG and SRK is necessary for the SI function, as plants carrying mutated or down-regulated SLG or SRK genes are self-fertile Goring et al 1993;Nasrallah et al 1994b;Conner et al 1997;Stahl et al 1998). The current model for SI in Brassica proposes that the pollen-borne ligand interacts with SLG and SRK, activates the SRK protein kinase and thus triggers a signal cascade that eventually leads to the rejection of self-pollen (Nasrallah et al 1994a).…”
Section: Introductionmentioning
confidence: 98%